Evaluasi Program Keterampilan Anak Berkebutuhan Khusus Di SLB ABC Taman Pendidikan Islam (TPI) Medan - Ade Triana Fauziah; Malida Putri; Mia Aulina Lubis (Publikasi Indonesia, 2022)
In education at special schools, one form of teaching is the provision of skills programs that aim to improve the skillful soul of students with special needs as their provision to live independently in the community later. This research was conducted at SLB ABC Taman Pendidikan Islam (TPI) Medan which aims to evaluate the skills program that is run at SLB ABC TPI Medan, which consists of 7 programs, namely catering, making accessories, delivering events, make-up, carpentry, sewing, dancing and making flower boards for students with visual impairments, hearing impairments, mental retardation and autism. The key informants of this study were the Principal of the ABC Special School Taman Pendidikan Islam Medan, the main informants were three SLB skill teachers who became mentors in the skills program, and additional informants were three parents of students who participated in the skills program. This study uses a qualitative approach with descriptive research methods, then the theory used is the CIPP program evaluation theory (context, input, process, product) by Stufflebeam. The results of this study are that in the four evaluation points, context evaluation and input evaluation were not successful, namely at the opportunity point in meeting needs and procedural design. Overall, however, the skills program was continued because it had fulfilled the objectives of meeting the needs of children with special needs who participated in the skills program.